Antioxidation Function of EGCG by Activating Nrf2/HO-1 Pathway in Mice with Coronary Heart Disease. (11th July 2022) - Huang, Xiaoyi; Chu, Yang; Ren, Hua; Pang, Xiaofen
Abstract : Objective . To explore the effect and mechanism of epigallocatechin gallate (EGCG) in mice with coronary heart disease (CHD). Methods . Firstly, a CHD model of mouse was established by feeding mice high-fat diet and randomly divided into four groups, including Model group (0.5% sodium cholate) and 10 mg/kg EGCG, 20 mg/kg EGCG, and 40 mg/kg EGCG groups. After oral administration of sodium cholate or EGCG, HE staining was conducted to assess the pathological changes of mouse cardiac tissues in each group of mice, biochemical kits to measure the levels of blood lipid and oxidative stress substance activity, and western blot to detect matrix metalloproteinase 2 (MMP-2), vascular endothelial growth factor (VEGFA), as well as expression levels of protein related to Nrf2/HO-1/NQO1 pathway in cardiac tissues. Results . The mice in the CHD model appeared to have myocardial pathological damage with elevated serum total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), and decreased high-density lipoprotein cholesterol (HDL-C). Of note, administration of EGCG significantly attenuated myocardial injuries and improved blood lipid levels in mice in a concentration-dependent manner. The advent of EGCG significantly decreased the expression of VEGFA and MMP-2 and increased the activity of superoxide dismutase (SOD), when reducing the content of reactive oxygen species (ROS) in the myocardial tissue and upregulating the expression of HO-1, NQO1, and Nrf2. Conclusion . EGCG may reduce atherosclerotic plaque and alleviate pathological damage in the cardiac tissue of CHD mice as well as improve blood lipid levels with antioxidative effect. The mechanism of its effect may be related to the activation of the Nrf2/HO-1/NQO1 antioxidant pathway in vivo of the CHD mice.